The Role of the Supervisory Agency in Enforcing Privacy and Data Security Laws in Indonesia - Irma Fatmawati; Rahmayanti (CV. Era Digital Nusantara, 2026)
The development of information technology and digitalization has increased the volume and complexity of personal data processing in Indonesia, thus posing serious challenges related to privacy protection and data security. In this context, the existence of a supervisory body plays a strategic role in ensuring regulatory compliance, particularly following the enactment of the Personal Data Protection Law (PDP Law). This study aims to analyze the role of the supervisory body in enforcing privacy and data security laws in Indonesia, including its supervisory functions, law enforcement, and the imposition of administrative sanctions. The method used is a normative juridical approach by analyzing laws and regulations and related literature. The results show that the supervisory body plays a significant role in creating legal certainty, raising awareness among business actors and the public, and encouraging the implementation of data protection principles. However, the effectiveness of this role still faces various obstacles, such as limited resources, inter-agency coordination, and low digital literacy among the public. Therefore, institutional strengthening, comprehensive derivative regulations, and increased human resource capacity are needed to achieve optimal personal data protection in Indonesia.